Optimization and Application of Spacing Parameter for Loosening Blasting with 24-m-High Bench in Barun Open-Pit Mine - Yin, Zuoming; Wang, Desheng; Wang, Xuguang; Dang, Zhiheng; Li, Wantao (Shock and vibration, 2021)
In view of the near slope blasting in Barun open-pit mine, which has merged sublevel mining, the operation safety conditions of middle-sized and large equipment in the second phase expansion are poor and need urgent improvement. To increase the efficiency of expansion and reduce costs, a 24-m-high bench and large spacing parameter for loosening blasting are proposed. The analysis of the physical mechanism of the stress wave attenuation in the rock indicates that the cylindrical charge is equivalent to several spherical charges. Considering the pressure attenuation, reflection, transmission, and superposition of the spherical charge after the equivalence, a double exponential function correction equation of the stress wave attenuation is obtained based on the Mises strength criterion. The stress of any point in the rock medium with various spacing parameter is obtained by calculation. ANSYS/LS-DYNA was used to simulate and study the stress distribution of a 24-m-high bench with various spacing parameter. Meanwhile, the accuracy of the correction equation was verified. The parameters of the high-bench blasting with good effect and low cost were determined to be 15 m  ×  5.5 m, and field tests were carried out. Results show that the large spacing parameter for 24-m-high bench loosening blasting in Barun open-pit mine is efficient and economical in medium-hard rock blasting. This study provides a reference for the practical exploration of the expansion of high benches in open-pit mines in China. The calculation error of the corrected double exponential function is near the numerical simulation result. It is suitable for all kinds of professional designers.